Yuri L’vovich Klimontovich - Zagorodny, A. (Condensed Matter Physics, 2004)
This issue is devoted to the memory of Professor Yu.L.Klimontovich, an outstanding
theorist whose ideas and works have been a great contribution to modern
kinetic theory and statistical mechanics.